Monitoring of rock stress change using instrumented rebar rock bolts. Issue 1 (August 2021) - Mai, W; Janiszewski, M; Uotinen, L; Mishra, R; Rinne, M
Abstract: Rock stress is causing unwanted deformations of deep underground spaces. Large deformations increase the risk of failure. The underground excavation causes rock stress changes in the surrounding rock mass, and the resulting deformations can be measured. In this paper, we present a method to monitor stress changes in the rock mass using rebar rock bolts instrumented with strain gauges to track the stress within the bolt. Next to that, we describe in-situ testing of this method using heating-induced stress in a natural underground environment. The heating experiment aims to create stress changes using rope heaters inserted into the rock mass and located symmetrically around a single instrumented rock bolt. The heat flux induced to the rock mass leads to volume expansion. The restricted thermal expansion causes an increase in the internal rock stress conditions. These conditions create a strain that can be measured and back-calculated as the rock stress change. The instrumented rock bolt and testing setup were installed in the Underground Research Laboratory located in a granitic rock below the Aalto University campus. The single bolt experiment demonstrates how instrumented rock bolts could monitor the changes in the rock mass stress state. The system can be used as a part of a real-time rock stress monitoring system in mining and rock engineering projects. The final part of the paper describes how this monitoring system can positively affect geotechnical risk management and increase the overall safety of underground construction.